Vibrant Architecture. Matter as a CoDesigner of Living Structures (2015)
Practical steps are established to enable a transition from industrial to ecological architectural practices. Using the parallel processing powers of the material world, a Nature-based production platform is informed, which evades traditional binary divisions that characterize modern architecture, such as Nature/machine, humanism/ environmentalism and matter/information. In dissolving these divisions that influence design decisions, I aim to increase the connectivity of architectural substrates and enable designers to explore new ways of thinking and making. In establishing the philosophical and cultural context for involving material properties in design solutions, I have drawn on Bennett’s notion of vibrant matter (Bennett, 2010), which invites us to recognize that we share a common ontology with matter through stardust (Science Daily, 1999; Sagan, 2007), which is intrinsically lively. The fabric of our existence can therefore respond directly to spatial programs, codesign events and ultimately exert collective effects through a new technological platform based on assemblages. The properties of this platform are experimentally demonstrated using chemistry at non- equilibrium states and in different contexts, which are further developed and critiqued in project work. Research findings are used to develop a manifesto that establishes a series of principles for the practice of vibrant architecture. The conceptual and practical transitions in my research demonstrate how matter may: